Effect of bacterial inoculants on the preservation and nutritive value of whole-plant corn silages - Bolsen, K.K.; Rice, D.W.; Hinds, M.A.; Zimmermann, C.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Inoculated and control corn silages were compare d using pilot-scale silos. Inoculated silages (Pioneer inoculant 117 4 and 1132) had significantly higher lactic to acetic acid ratios, and numerically lower values for DM loss, acetic acid, ethanol, and ammonia-nitrogen than the control silage—evidence that both inoculants produced a more efficient fermentation . Although the inoculated silage rations had higher DM intakes than the control, nutrient digestibilities were similar for the three silages . These results are consistent with numerous studies that compared untreated and inoculant-treated silages over a wide range of crops and ensiling conditions in our research during the past several years.
Keywords: Beef; Silage; Innoculant; Preservation; Corn